Uji Aktivitas Antibakteri Ekstrak Etanol Daun Kamboja Putih (Plumeria acuminata) Terhadap Pertumbuhan Streptococcus mutans (Antibacterial Activity Of Etanol Extract Of White Frangipani leaf (Plumeria acuminata) Against The Growth Of Streptococcus mutan - Affian Hudatama Putra; Yani Corvianindya Rahayu (Pustaka Kesehatan, 2017)
Background : Most of caries are caused by Streptococcus mutans. Etanol extract of white frangipani leaf are supposed to inhibit the growth of Streptococcus mutans. This extract contains antibacterial compound such us flavonoid, saponin, tannin, and alkaloid. Purpose : This study was to determine the antibacterial activity of etanol extract of white frangipani leaf in variant concentration on growth of Streptocossus mutans. Method : This study was used well diffusion method with 6 treatment groups. Each petridish were filled BHI-A and inoculated by S. mutans followed by making 6 wells using the borer (diameter 5 mm) and filled 20 µL of white frangipani leaf extract 50%, 25%, 12,5%, 6,25%, povidone iodine as positive control, and aquadest sterile as negative control into the well. Each petridish were incubated at 37ºC for 24 hours. The inhibitory zones were measured by using digital calliper. Results: The result showed that there were inhibitory zones in positive control, extract 50%, and 25% treatment groups and there is no inhibitory zones in negative control, extract 12,5%, and 6,25%. Conclusion: Etanol extract of White frangipani leaf has antibacterial activity against the growth of Streptococcus mutans with minimum inhibitory concentration of 25% . Keywords : Antibacterial activity, Streptococcus mutans, Etanol extract of white frangipani leaf.